Anti-Inflammatory Effect of a Polyphenol-Enriched Fraction from Acalypha wilkesiana on Lipopolysaccharide-Stimulated RAW 264.7 Macrophages and Acetaminophen-Induced Liver Injury in Mice. (7th August 2018) - Wu, Hongtan; Pang, Haiyue; Chen, Yupei; Huang, Lisen; Liu, Huaxin; Zheng, Yongbiao; Sun, Cuiling; Zhang, Gang; Wang, Gueyhorng
Abstract : A polyphenol-enriched fraction (PEF) from Acalypha wilkesiana, whose leaves have been traditionally utilized for the treatment of diverse medical ailments, was investigated for the anti-inflammatory effect and molecular mechanisms by using lipopolysaccharide- (LPS-) stimulated RAW 264.7 macrophages and acetaminophen- (APAP-) induced liver injury mouse model. Results showed that PEF significantly attenuated LPS-induced nitric oxide (NO) and prostaglandin E2 (PGE2 ) production and suppressed the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX-2) in RAW 264.7 macrophages. PEF also reduced the secretion of proinflammatory cytokines including tumor necrosis factor- α (TNF- α ), interleukin- (IL-) 1 β, and IL-6 in LPS-stimulated RAW 264.7 macrophages. Moreover, PEF potently inhibited LPS-induced phosphorylation of mitogen-activated protein kinases (MAPKs) as well as the activation of nuclear factor- κ B (NF-κB) by preventing the degradation of inhibitor κB- α (IκB- α ). In vivo, PEF pretreatment ameliorated APAP-induced liver injury and hepatic inflammation, as presented by decreased hepatic damage indicators and proinflammatory factors at both plasma and gene levels. Additionally, PEF pretreatment remarkably diminished Toll-like receptor 3 (TLR3) and TLR4 expression and the subsequent MAPKs and NF- κ B activation. HPLC analysis revealed that two predominantly polyphenolic compounds present in PEF were geraniin and corilagin. These results indicated that PEF has an anti-inflammatory effect, and its molecular mechanisms may be involved in the inactivation of the TLR/MAPK/NF- κ B signaling pathway, suggesting the therapeutic potential of PEF for inflammatory diseases.